الفايسبوك وعلاقته بالتنشئة الإجتماعية للشباب - رمضاني, محمد; كهمان, منصف (University of Eloued جامعة الوادي, 2021)
Résumé de l'étude Our study dealt with the topic of Facebook and its relationship with the socialization of youth, and we relied on the questionnaire as a basic tool for data collection and interview, and we also used a descriptive approach that is appropriate to the nature of our study topic. : Communication, education, organization, that is, we did a comprehensive survey of the study community, and the statistical methods represented in the percentages and the statistical package spss program were adopted. The results of the study revealed that Facebook contributes to creating new patterns and habits for young people that will take root with them over time, enable young people to communicate with others in an easy way, as well as influence their values and habits and integrate them with extraneous customs and cultures, which may not coincide with their habits and orientations.
دراسة ميدانية على عينةمن طلبة جامعة الشهيد حمه لخضربالوادي
مذكرة ماستر في علم اجتماع واتصال تخصص علم اجتماع الاتصال
Keywords: مواقع التواصل الاجتماعي، التنشئة الاجتماعية، الفايسبوك; Sites de réseaux sociaux, socialisation, Facebook; Social networking sites, socializing, Facebook